Praktik Pemberian Makan dan Perilaku Picky Eater pada Anak Usia Prasekolah - Susi Muryani; Afi Fatuz Zahro; Nurhakim Yudhi Wibowo (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Introduction: Feeding practices carried out by parents greatly affect children's eating behavior, especially picky eater behavior which often occurs among preschool children characterized by difficult eating behavior, and picky eating.Objective: knowing the relationshipMethod: using descriptive correlation research design with a cross sectional approach. The sampling technique uses total.Results: data analysis using Pearson Product Moment with Kendalls Tau-b test obtained P value = 0.002 <0.005, it can be concluded that there is a relationship between feeding practices and picky eater behavior in preschool children at TK Negeri Pembina Tarub.Conclusion: parents are encouraged to provide proper feeding practices to be able to form good and healthy eating behavior, especially in preschool children.